PENGARUH KEGIATAN MAJELIS TAKLIM MUSHOLA AL-MANBAUL ISLAM TERHADAP SOLIDARITAS SOSIAL DI DESA PANIIS - Mohammad Syahru Assabana (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
This research background is the social solidarity behavior of mothers has not met expectations, even though the activities of the Al-Manbaul Islam Mosque’s Taklim Assembly have been good. The researcher used quantitative methods, where the data collection techniques were observation, interviews, questionnaires, and documentation. The data analysis techniques were quantitative analysis and correlation test. The result indicates that the activities of the Al-Manbaul Islam Mosque’s Taklim Assembly are weekly recitation, holy yasin, holy sholawat or marhaban, aqiqah, and qurban. Based on data obtained from 20 respondents, the average is 86% and is almost located in always area. The congregation's social solidarity is 84%, close to the always category. The influence of Taklim Assembly activities with the social solidarity of the congregation’s mothers of the Al-Manbaul Islam Mosque shows a correlation value that reaches 0.71, close to a high or strong correlation because it is in the interval 0.70 – 0.90. This means that the stronger activities of the Al-Manbaul Islam Mosque’s Taklim Assembly, the better social solidarity it becomes.